Use of conductive zip and Velcro as a polarisation reconfiguration means of a textile patch antenna. Issue 7 (16th April 2020) - Tsolis, Aris; Michalopoulou, Asimina; Alexandridis, Antonis A.
Abstract : Α feasibility study of using components such as conductive Velcro tape and zip fastener to change the polarisation of a textile patch antenna from linear (LP) to circular (CP) is presented. The antennas are designed to operate at 2.3–2.5 GHz frequency band, are made using felt substrate and conductive cloth and their size is 100.4 mm × 74.2 mm × 4.26 mm. It is proved, via simulations and measurements, that such components are strong candidates as means for polarisation reconfiguration of textile antennas. Both Velcro and zip textile patch antennas at the LP mode yield axial ratio (AR) larger than 10 dB at the operating frequency range. In the CP mode, the Velcro antenna gives AR equal to 3.1 dB at 2.35 GHz and the zip antenna 1 dB at 2.31 GHz. Repeatability measurements of interchanging polarisation modes (LP–CP) for both antennas have been conducted presenting acceptable repeatability. Great advantage of both antennas (Velcro and zip) is that the polarisation can be changed at will by a simple manipulation (detach the Velcro or unzip); thus, providing to the user the flexibility of adjusting the antenna characteristics depending on wearable application and environment of operation.